Pengaruh Stres Kerja Dan Manajemen Waktu Terhadap Kinerja Karyawan Dengan Kepuasan Kerja Sebagai Variabel Intervening Pada Dinas Perdagangan Kota Padang - Maria Florella; Dori Mittra Candana; Mardhatila Fitri Sopali (CV. ITTC INDONESIA, 2026)
This study aims to determine and analyze the effect of work stress and time management on employee performance with job satisfaction as an intervening variable at the Padang City Trade Office. This research uses a quantitative approach with a survey method through questionnaires distributed to 30 respondents who are employees of the Padang City Trade Office. The data analysis technique used is path analysis with the assistance of SmartPLS software. The results show that work stress has a significant effect on job satisfaction. Time management also has a significant effect on job satisfaction. Furthermore, work stress has a significant effect on employee performance, while time management does not have a significant effect on employee performance. Job satisfaction has a significant effect on employee performance. In addition, job satisfaction is proven to mediate the effect of work stress on employee performance and also mediates the effect of time management on employee performance. These findings indicate that improving employee performance is not only directly influenced by work stress and time management but also indirectly through job satisfaction as a psychological factor that strengthens the relationship. Therefore, the Padang City Trade Office needs to pay attention to managing work stress and implementing effective time management to enhance job satisfaction and optimize employee performance.